Plant Defense Responses Induced by Two Herbivores and Consequences for Whitefly Bemisia tabaci - Lin, Dan; Xu, Yonghua; Wu, Huiming; Liu, Xunyue; Zhang, Li; Wang, Jirui; Rao, Qiong (Frontiers in Physiology, 2019)
Diverse herbivores are known to induce various plant defences. The plant defences may detrimentally affect the performance and preference to subsequent herbivores on the same plant, such as by affecting another insect’s feeding, settling, growth or oviposition ability. The whitefly Bemisia tabaci and the mealybug Phenacoccus solenopsis are common sap-sucking pests, have broad host distributions, and can coexist on the same plant in the field. The carmine spider mite Tetranychus cinnabarinus, a cell-content feeder, is equally an important economic pest. In this study, two diverse herbivores (T. cinnabarinus and P. solenopsis) were used to pre-treat cucumber to explore the impact on a later-colonizing species, B. tabaci. Subsequently, the defensive enzymes (PAL and LOX) of treated plants and their associated genes of JA, SA or ET pathways were analyzed. Compared with the control group, B. tabaci tend to select cucumbers pre-treated by spider mites, rather than plants pre-treated by mealybugs. And the amount of egg laid is related to the preference. The results also showed that T. cinnabarinus was more likely to activate plant jasmonic acid regulated genes, while mealybugs were more likely to activate key genes regulated by salicylic acid. Those may be one of the essential factors that affects the resistance of host plants to B. tabaci. Moreover, B. tabaci was more sensitive to plants coexisting with P. solenopsis; this may be attributed to the increase in digestive enzyme activity and protective enzyme activity of whitefly. In conclusion, T. cinnabarinus and P. solenopsis induced different plant defence activities on the same host plant. Through the variation of the defence enzyme activity and the gene expression level of the defence pathway, it affected the subsequent performance and preference of the whitefly. Simultaneously, the digestive enzymes and protective enzymes of the whitefly also play a substantial regulatory role in its settling and oviposition ability.